μ-opioid receptor system mediates reward processing in humans - Nummenmaa, Lauri; Saanijoki, Tiina; Tuominen, Lauri; Hirvonen, Jussi; Tuulari, Jetro J.; Nuutila, Pirjo; Kalliokoski, Kari (Nature communications, 2018)
The endogenous μ-opioid receptor (MOR) system regulates motivational and hedonic processing. We tested directly whether individual differences in MOR are associated with neural reward responses to food pictures in humans. We scanned 33 non-obese individuals with positron emission tomography (PET) using the MOR-specific radioligand [ 11 C]carfentanil. During a functional magnetic resonance imaging (fMRI) scan, the subjects viewed pictures of appetizing versus bland foods to elicit reward responses. MOR availability was measured in key components of the reward and emotion circuits and used to predict BOLD-fMRI responses to foods. Viewing palatable versus bland foods activates regions involved in homeostatic and reward processing, such as amygdala, ventral striatum, and hypothalamus. MOR availability in the reward and emotion circuit is negatively associated with the fMRI reward responses. Variation in MOR availability may explain why some people feel an urge to eat when encountering food cues, increasing risk for weight gain and obesity. μ-opioid signalling has a known role in the response to various rewarding stimuli, including pleasant foods. Here, Nummenmaa et al. show using PET and fMRI that individual differences in brain μ-opioid receptor density predict the strength of the neural response to highly palatable foods in humans